Evaluasi Program Keluarga Harapan (PKH) di Kecamatan Rumbai, Kota Pekanbaru - Alexsander Yandra; Husni Setiawan; Nurmanisa Sella; Prihati Prihati; Tatum Derin (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2020)
This article discusses the evaluation of the Family Hope Program (PKH) in Sri Meranti Village, Rumbai District, Pekanbaru City. Since 2007 the PKH program was created and implemented, even distribution of the program remains a problem that needs to be tracked comprehensively. Sri Meranti Village is the largest recipient of aid in all Rumbai District but still not evenly distributed. This study aims to evaluate the PKH program in Sri Meranti Village, Rumbai District, Pekanbaru City. With a research question how is the implementation of the Family of Hope Program in Sri Meranti Village. The research methodology is descriptive qualitative with the selection of purposive informants and data obtained by in-depth interview techniques. Data collected in the form of primary and secondary data and analyzed ethically and emically by William Dunn's evaluation theory approach. The findings of this study are the PKH in Sri Meranti Village, Rumbai District, Pekanbaru City and the amount of aid has increased every year. However, the Sri Meranti Kelurahan community still considers aid to be uneven because there are still poor families who do not receive PKH funding.